Pengaruh Implementasi Sistem Informasi Manajemen Daerah, Kualitas Sumber Daya Manusia dan Penerapan Standar Akuntansi Pemerintah Terhadap Kualitas Laporan Keuangan Pemerintah - Agustina Mutia; Achyat Budianto; Mistiani Mistiani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of SIMDA, HR quality and SAP implementation on the quality of government financial reports at the Regional Financial and Asset Management Agency of Merangin Regency. This study uses a quantitative approach with primary data in the form of observations, interviews and questionnaires. Sampling in this study used a purposive sampling technique with a sample of 40 people. In this study using multiple linear regression analysis and testing the hypothesis on the T test and F test and analysis of the coefficient of determination. The results of this study indicate that the implementation of regional management information systems and the quality of human resources have no significant effect on the quality of government financial reports, while the research results for the variable of application of government accounting standards show that they have a significant effect on the quality of financial reports. For simultaneous test results (F test), namely the implementation of regional management information systems, the quality of human resources and the application of government accounting standards have a joint effect on the quality of government financial reports. The results of the coefficient of determination (R2) show that the independent variables namely SIMDA implementation, HR quality and SAP implementation can explain the variable quality of government financial reports by 61%, the remaining 31% is influenced by other variables not examined in this study.